1979
DOI: 10.1002/app.1979.070230604
|View full text |Cite
|
Sign up to set email alerts
|

Aspects of the thermal and dynamic mechanical behavior of EPDM rubbers

Abstract: SynopsisThe influence of both ethylene content and the degree of crystallinity on the thermal and dynamic mechanical properties of certain commercial EPDM rubbers were investigated using the TMA, DSC, and Rheovibron techniques. The six materials chosen for this study were Nordel 1560, Intolan 260, Royalene 1812, Vistolan 3708, Intolan 255, and Keltan 778.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1995
1995
2010
2010

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…This shows that EPDM/NBR is cross-linked and the interaction between the EPDM/NBR and the iPP has increased. Hourston and Byrne [30,31] investigated that the dynamic mechanical behavior of EPDM and reported that the tan δ max is increased by cross-linking which is shown with the decrease of the degree of crystallinity from 41.65 to 23.75 as the loading of EPDM/NBR content increases from 0 to 40 wt. % in the blend.…”
Section: Dynamic Mechanical Analysis (Dma)mentioning
confidence: 96%
See 1 more Smart Citation
“…This shows that EPDM/NBR is cross-linked and the interaction between the EPDM/NBR and the iPP has increased. Hourston and Byrne [30,31] investigated that the dynamic mechanical behavior of EPDM and reported that the tan δ max is increased by cross-linking which is shown with the decrease of the degree of crystallinity from 41.65 to 23.75 as the loading of EPDM/NBR content increases from 0 to 40 wt. % in the blend.…”
Section: Dynamic Mechanical Analysis (Dma)mentioning
confidence: 96%
“…The uncross-linked blends were designated as iPP 100 , iPP 90 EUC 10 , iPP 80 EUC 20 , iPP 70 EUC 30 and iPP 60 EUC 40 and cross-linked blends were designated as iPP 90 EC 10 , iPP 80 EC 20 , iPP 70 EC 30 and iPP 60 EC 40, the subscripts indicates the amount of iPP and EPDM/NBR respectively in the blends.…”
Section: Blend Formulationmentioning
confidence: 99%
“…This indicates that the EPDM is crosslinked and the interaction between the EPDM and the PP has increased. Byrne and Hourston9, 10 investigated the dynamic mechanical behavior of EPDM and reported that the tan max is increased by crosslinking, which is ascribed to the decrease of the degree of crystallinity from 41.63 to 23.73 as the EPDM content increases from 0 to 40 wt % in the blend. The same phenomenon was observed by Coran and Patel 11.…”
Section: Resultsmentioning
confidence: 99%
“…Rinde and Hoge8, 9 constructed the master curve of dynamic shear modulus of polystyrene bead foams and solid polymer for different frequencies as well as for a wide range of temperatures. The linear elastic properties of microcellular plastics have been reported by Jackson et al10 Strain‐dependent dynamic mechanical properties of solid rubbers are reported by several workers,11–20 whereas very little work on closed cell microcellular rubbers has been investigated. The studies on the viscoelastic behaviors of closed cell microcellular ethylene–octene copolymer21–23 show that the storage modulus and tan δ (the ratio of loss modulus and storage modulus) are frequency‐ and temperature‐dependent, and the log of storage modulus bears a linear relationship with the log of density.…”
Section: Introductionmentioning
confidence: 94%